The Intersection of Mental Illness, Homelessness & Incarceration - Santos, Megan (My University, 2021)
Over the summer of 2021, research was conducted to analyze the relationship between mental illness, homelessness, and incarceration. This research consisted of a 15-part survey of half demographic and half open-ended long answer questions ultimately compiling a qualitative analysis. The intention of creating a survey with open ended questions was to provide a platform for people who have mental illness and are homeless and/or have been incarcerated to share their stories, concerns, and service needs to inform policy literature. A very specific and difficult to reach population group was sought after, this turned out to yield much different results than expected. Instead of accessing the intended group of people, the author got connected with a person from a group of people who have previously been homeless, have mental illness, and dedicate their time to helping others who are currently homeless. Instead of finding a way for far-away researchers to gather stories from people who are currently homeless, this research led to inspiration from those people and instead a suggestion for a more ethical point of access to vulnerable populations. This research illustrates and confirms that vulnerable populations are most ethically researched and reached out to by people who come from shared lived experiences.